Direct Access to Unique C‐5'‐Acyl Modified Nucleosides through Liebeskind–Srogl Cross‐Coupling Reaction. Issue 21 (27th October 2021) - Maverick, Mary Anne; Gaillard, Marie; Vasseur, Jean‐Jacques; Debart, Françoise; Smietana, Michael
Abstract: The chemical functionalization at C‐5' position of nucleosides has been significantly less studied compared to the C‐1', C‐2' and C‐3' sugar positions in spite of its potential important role for biological activity. We describe here the synthesis of new carbothioate nucleosides which were then engaged in a Liebeskind‐Srogl reaction with various boronic acids for the preparation of diversely modified C‐5'‐acyl nucleosides. Applied to pyrimidine nucleosides in the DNA and RNA series, the reaction showed a broad substrate scope and more than 25 examples were synthesized in good‐to‐excellent isolated yields. This general and efficient Pd‐catalyzed and Cu(I)‐mediated cross‐coupling represents a convenient method to prepare a diverse set of 5'‐modified nucleosides and paves the way for further transformation into a variety of potentially bioactive compounds via the possible conversion of the C‐5'‐ketone. Abstract : An efficient palladium/CuTC cocatalyzed cross‐coupling reaction procedure for the synthesis of C‐5'‐acyl nucleosides from the corresponding nucleoside 5′‐carbothioates and boronic acids is described. The procedure is fast, efficient, and it tolerates a wide variety of functionalities, thus expanding the so far limited chemical methods for C‐5' diversification of deoxy‐ and ribonucleosides.